2019
DOI: 10.1038/s41598-019-47114-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional HepaRG spheroids as a liver model to study human genotoxicity in vitro with the single cell gel electrophoresis assay

Abstract: Many efforts have been made in the last 30 years to develop more relevant in vitro models to study genotoxic responses of drugs and environmental contaminants. While 2D HepaRG cells are one of the most promising models for liver toxicology, a switch to 3D cultures that integrate both in vivo architecture and cell-cell interactions has occurred to achieve even more predictive models. Preliminary studies have indicated that 3D HepaRG cells are suitable for liver toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 41 publications
(59 reference statements)
3
53
0
Order By: Relevance
“…Several studies have shown differences in sensitivity to induced toxicity in 3D and 2D cultures [25,[27][28][29]73,78]. We have previously found similar cytotoxicity in 2D and 3D HepG2 cultures, but higher sensitivity in the 3D culture for induced DNA damage by MMS [27].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Several studies have shown differences in sensitivity to induced toxicity in 3D and 2D cultures [25,[27][28][29]73,78]. We have previously found similar cytotoxicity in 2D and 3D HepG2 cultures, but higher sensitivity in the 3D culture for induced DNA damage by MMS [27].…”
Section: Discussionsupporting
confidence: 57%
“…We have previously found similar cytotoxicity in 2D and 3D HepG2 cultures, but higher sensitivity in the 3D culture for induced DNA damage by MMS [27]. Increased sensitivity in genotoxicity was also seen after exposure to 11 chemicals in a HepaRG spheroid model [29]. In agreement with this, benzo(a)pyrene and 2-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine, which both require metabolic activation for induction of genotoxicity, induced a higher micronucleus frequency in HepG2 spheroids compared to monolayer cultures [28].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For genotoxicity assessment, robust protocols for 3D models have been established for skin, airways and liver tissue equivalents [ 10 , 197 ]. Many of the 3D cell culture systems applied in genotoxicity testing (of NMs) have been spheroids, such as liver spheroids constructed from primary hepatocytes, HepG2 hepatocellular carcinoma cells or the HepaRG cell line applied to the comet assay [ 14 , 31 , 34 , 198 , 199 ] and micronucleus assay [ 200 ]. Human 3D airway models usually consist of a functional and differentiated respiratory epithelium with cilia and mucus and are cultured on the physiological relevant air-liquid-interface (ALI) [ 19 ].…”
Section: New Advanced In Vitro Models (3d Organ-on-a-chip)mentioning
confidence: 99%
“…Further, cells in spheroid cultures secrete an extracellular matrix in which they reside, and they can interact with cells from their original microenvironment [ 31 ]. Spheroids can also be formed from human cancer-derived hepatocytes, such as HepaRG cells [ 32 , 33 , 34 ], HepG2 cells [ 35 , 36 , 37 ], and Huh-7 cells [ 38 ]. Cultured human cancer-derived hepatocytes have long been used for human-specific toxicity assessments, but they generally have lower expression levels of drug-metabolizing enzymes than PHHs [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%